Penggunaan Media Pembelajaran (Wordwall) sebagai Inovasi pada Mata Pelajaran Non-Kejuruan di SMK PGRI 1 Kota Serang : (Studi Deskriptif Pada Peserta Didik Kelas X) - Oktavia Theresia Ompu Sunggu; Muhammad Atma Taher; Atik Rositah; Kirana Dewi; Ferdansyah Putra; Suhendar Suhendar (Jurnal Bintang Pendidikan Indonesia, 2024)
The research aims to find out and describe how to use Wordwall learning media in the learning process of non-major subjects among Class X students of SMK PGRI 1 Kota Serang. This research uses descriptive qualitative research with data collection through observation, interviews, and documentation. Qualitative data analysis carried out includes data collection, data reduction, data presentation and conclusions. Efforts are made by utilizing technology as a learning medium. Based on the results of the research, the use of Wordwall in learning non-major subjects among Class X students of SMK PGRI 1 Kota Serang is used to increase innovation in learning. Through Wordwall in attendance, listening to material, and collecting assignments given can be seen and reviewed through various complete features that teachers can utilize in meaningful learning.